2021
DOI: 10.3389/fenvs.2021.657969
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Cooling Effect of Pocket Green Space in High Density Urban Areas in Shanghai, China

Abstract: Recently, pocket green spaces (PGS), i.e., small green spaces, have attracted growing attention for their various ecological and social services. As a crucial part of urban green spaces in high-density urban areas, PGS facilitates recreation and relaxation for neighborhoods and thus improves the livability of cities at the local scale. However, whether and how the PGS cools the urban heat island effect is still unclear. This research was performed in the highly developed areas of the city of Shanghai during ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 95 publications
3
23
0
Order By: Relevance
“…Therefore, how to scientifically configurate the landscape elements and improve ecological service function of urban parks, especially their cooling effect, has become an urgent problem that need to be solved. Previous studies about effects of urban green space on thermal environment were reported in Shanghai, which mainly concentrated on the relationship between LST and green space pattern combined with landscape metrics from the urban landscape scale [ 48 , 49 , 50 ], the cooling effects of specific park features (e.g., park size), single landscape elements (e.g., water body) or single park type (e.g., pocket parks) [ 51 , 52 , 53 ] and thermal comfort and space use in a specific park by meteorological measurements [ 40 ]. However, a clear understanding of the composition and morphological characteristics under different scale levels of urban parks and their quantitative impact on the LST inside and in the surrounding of the parks in a time-series analyses, is still a lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, how to scientifically configurate the landscape elements and improve ecological service function of urban parks, especially their cooling effect, has become an urgent problem that need to be solved. Previous studies about effects of urban green space on thermal environment were reported in Shanghai, which mainly concentrated on the relationship between LST and green space pattern combined with landscape metrics from the urban landscape scale [ 48 , 49 , 50 ], the cooling effects of specific park features (e.g., park size), single landscape elements (e.g., water body) or single park type (e.g., pocket parks) [ 51 , 52 , 53 ] and thermal comfort and space use in a specific park by meteorological measurements [ 40 ]. However, a clear understanding of the composition and morphological characteristics under different scale levels of urban parks and their quantitative impact on the LST inside and in the surrounding of the parks in a time-series analyses, is still a lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The protection of green areas and the creation of new ones, even of a small scale, such as pocket parks, is an important direction of spatial policy, aimed at increasing the accessibility of public spaces and improving environmental conditions [65,66]. On the other hand, as the distance from the city center increases, the indicators for the floor area and groos floor area of shopping centers development are clearly decreasing.…”
Section: Discussionmentioning
confidence: 99%
“…They are also used in circular economy strategies and in the sustainability challenges of cities in the use of resources, such as water, energy and food [ 109 ]. In this sense they are now considered as a “critical element in addressing Sustainable Development Goals 11”, which is related to “sustainable cities and communities” [ 110 ], such as climate change adaptation measures [ 111 ], considering the cooling and urban heat mitigation effects of even small pocket green spaces in high density urban areas [ 112 ], or the specific benefits of vegetated green roofs and city trees on stormwater management for urban resilience [ 113 ].…”
Section: Urban Practices To Mitigate Soil Sealing: Typologies Charact...mentioning
confidence: 99%